In Silico Analysis of Phalaenopsis Orchid Homeobox1 (POH1) Functional Gene for Shoot Development in Phalaenopsis Orchid - Rasjid, Nuzlan; Kurniawan, Febri Yuda; Putri, Saifa Usni; Linggabuwana, Aviesta; Prasojo, Ireneus Seno; Semiarti, Endang (Journal of Tropical Biodiversity and Biotechnology, 2023)
The most favorite ornamental crop in Indonesia is orchid which benefited as floriculture. Therefore, the quality of this crop must be improved.  Biotechnology is appropriate to be used to improve the quality and quantity of orchid plants. To conduct this method, researchers must know what genes function in plant development. In Phalaenopsis orchids, the gene has been identified as homeobox genes called Phalaenopsis Orchid Homeobox1 (POH1). This research aims to conduct in silico analysis of the gene. The materials were retrieved from mRNA and amino acid databases. Then, the materials are aligned, visualized, motif location analysis, motif function discovery, phylogenetic construction, and protein 3D structural modelling. Based on mRNA and amino acid alignment, there are 4 domain regions that are conserved in POH1 and other homologous genes, such as KNOX1, KNOX2, ELK Domain, and Homeobox KN Domain, which roles as a transcription factor involved in plant development. SWISS-MODEL and ColabFold were used in protein modelling of the protein. By ColabbFold modelling, the modelling prediction uses 325 residues, higher than SWISS-MODEL in 59 residues. ColabFold validation by Ramachandra Plot depicts having the most favourite regions is 68.6%, while SWISS-MODEL is 92.3%. Another validation parameter is overall quality factor and QMEAN Score. Protein modelling by ColabFold has overall quality factor 89.252 and QMEAN Score 0.41 ± 0.05. However, SWISS-MODEL 3D prediction has overall quality factor 98.039 and QMEAN score of 0.71 ± 0.11.